Religion and Employees Fraud Prevention: With Moderation of Spirituality, Leadership and Oganizational Culture - Rian Abrori; Auliya Zulfatillah; Habi Bullah (JAFFA, 2022)
This study aims to define and analyse the relationship between religiosity and Employees Fraud Prevention with spirituality, leadership dan organizational culture as a moderating variable. The data analysis method used in this research is in the form of multiple linear regression testing and interaction test or moderated regression analysis (MRA). The population in this reseach is Baitul Mal Wattamwil Nuansa Ummah (BMT NU) and Baitul Mal Wattamwil Sidogiri Integrated Joint Venture (BMT UGT Sidogiri) spread across Madura Island. The result indicate that the Religiosity and spirituality Variable affects the employees fraud prevention. This study also verifies that Leadership and Organizational Culture cannot moderate the effect of religiosity on employees fraud prevention.